Empowering Communities : The Local Initiatives Support Program in Russia - Shulga, Ivan (World Bank, Washington, DC, 2014)
Prosperity from economic growth is not shared evenly among Russia's population and regions. Local communities and rural territories face serious development challenges: including poor living conditions, infrastructure, and services and lack of citizens' participation in decision-making processes. The Russian Federation Local Initiatives Support Program (RF LISP) aims to address community challenges by introducing a participatory approach to the development and rehabilitation of local-level social infrastructure. Specifically, LISP channels funds from regional budgets to finance participatory projects in poorer local communities. For the period 2009-14, LISP has been implemented in six regions and has resulted in more than 1,200 projects with over 1 million beneficiaries. Key factors for LISP success are the following: (i) mainstreaming of LISP into the national administrative system and budget process, and (ii) providing the Bank's technical assistance at all stages of project implementation to share international experience in community-driven development (CDD) projects, and ensuring transparency and quality of LISP procedures.